A virtual simulation approach to assess the effect of trocar-site placement and scar characteristics on the abdominal wall biomechanics - Tuset, Lluís; López-Cano, Manuel; Fortuny, Gerard; López, Josep M.; Herrero, Joan; Puigjaner, Dolors (Scientific reports, 2024)
Analyses of registries and medical imaging suggest that laparoscopic surgery may be penalized with a high incidence of trocar-site hernias (TSH). In addition to trocar diameter, the location of the surgical wound (SW) may affect TSH incidence. The intra-abdominal pressure (IAP) exerted on the abdominal wall (AW) might also influence the appearance of TSH. In the present study, we used finite element (FE) simulations to predict the influence of trocar location and SW characteristics (stiffness) on the mechanical behavior of the AW subject to an IAP. Two models of laparoscopy patterns on the AW, with trocars in the 5–12 mm range, were generated. FE simulations for IAP values within the 4 kPa–20 kPa range were carried out using the Code Aster open-source software. Different stiffness levels of the SW tissue were considered. We found that midline-located surgical wounds barely deformed, even though they moved outwards along with the regular LA tissue. Laterally located SWs hardly changed their location but they experienced significant variations in their volume and shape. The amount of deformation of lateral SWs was found to strongly depend on their stiffness. Trocar incisions placed in a LA with non-diastatic dimensions do not compromise its mechanical integrity. The more lateral the trocars are placed, the greater is their deformation, regardless of their size. Thus, to prevent TSH it might be advisable to close lateral trocars with a suture, or even use a prosthetic reinforcement depending on the patient's risk factors (e.g., obesity).